Important Soft Skills to Promote Youth Employment in Algeria (مجلة الواحات للبحوث والدراسات, 2023)
AbstractThis Paper Suggests That Algerian Youth Need To Develop A Set Of Specific Skills In Order To Gain Access To Employment, Or Create Their Own Business. The Current Research Aims At Identifying Some Important Skills That Can Help Youth Overcome The Challenges They Face In The Algerian Employment Context; It Also Presents Some Career Projects’ Initiatives In Algeria That Have Already Succeeded In Building Many Necessary Soft Skills. A Questionnaire Was Administered To 3rd Year License And Master II Language Sciences EFL Students At Badji Mokhtar Annaba University In Order To Investigate Their Self-Perceived Soft Skills Level. The Findings Revealed That EFL Students Have An Average To A Decent Level Of Soft Skills That Is Needed In The Workplace. Yet More Efforts Are Still Required To Improve Those Crucial Skills.Keywords: Soft Skills, Youth Employment, Job Search, Skills Gap, Career Projects.